The Relationship Between Knowledge Level and Clean and Healthy Living Behavior Towards Students' Self-Efficacy at Muhammadiyah 1 Vocational School, Kepanjen - Muchammad Imam Ma'ruf; Agus Tinus; Kuncahyono Kuncahyono (Journal of General Education and Humanities, 2026)
Infectious disease prevention among vocational high school (SMK) students remains suboptimal due to inconsistencies between knowledge and actual health behavior. This study aims to analyze the role of self-efficacy by examining the influence of knowledge and Clean and Healthy Living Behavior (PHBS). A quantitative cross-sectional correlational design was applied, involving 100 students selected by random sampling. Data were collected using structured questionnaires and analyzed using correlation tests. The results show that knowledge has no significant relationship with self-efficacy (r ≈ 0.100; p > 0.05), whereas PHBS demonstrates a strong, significant positive correlation (r = 0.770; p < 0.05). These findings indicate that self-efficacy is more strongly shaped by behavioral practice than by cognitive understanding, supporting social cognitive theory. In conclusion, strengthening practical health behavior is more effective than solely improving knowledge in enhancing students’ self-efficacy for disease prevention.